2013
DOI: 10.1142/s1793292013500689
|View full text |Cite
|
Sign up to set email alerts
|

Chiseled Nickel Hydroxide Nanoplates Growth on Graphene Sheets for Lithium Ion Batteries

Abstract: The morphologies and structures of Ni(OH) 2 -graphene hybrid materials were tailored by using di®erent mineralizers in this work. It was revealed that the synergic e®ects of the highly oxidized graphene sheets and the mineralizers played a crucial role in controlling the morphology and structure of the nanocomposites, and Na 2 CO 3 is a very e®ective mineralizer for growing chiseled 2D nanoplates of Ni(OH) 2 on graphene sheets. When produced with NaOH, fragmental Ni(OH) 2 crystals with irregular shapes erratic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Because of the much higher N doping degree (N content is 13.1% determined by XPS) of NDG in this work, there could be higher concentration of N defects and other imperfections in the graphene domains, and thus exhibited the lower crystallinity of NDG, which can be confirmed by the XRD results (Figure S 1d). The broad D (1360 cm –1 ), G (1580 cm –1 ), and 2D (∼2800 cm –1 ) bands of Raman spectroscopy (Figure S1e) also confirm this disordered structure. The intensity ratio of D to G is 2.47, indicating a considerable number of structure defects in NDG . The type H3 hysteresis loop of nitrogen adsorption–desorption isotherm (Figure S1f), suggesting the slit-shaped pores between parallel graphene layers of NDG. , The calculated Brunauer-Emmett- Teller (BET) specific surface area of NDG is 398 m 2 g –1 , verified that the NDG are the few-layer graphene sheets.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Because of the much higher N doping degree (N content is 13.1% determined by XPS) of NDG in this work, there could be higher concentration of N defects and other imperfections in the graphene domains, and thus exhibited the lower crystallinity of NDG, which can be confirmed by the XRD results (Figure S 1d). The broad D (1360 cm –1 ), G (1580 cm –1 ), and 2D (∼2800 cm –1 ) bands of Raman spectroscopy (Figure S1e) also confirm this disordered structure. The intensity ratio of D to G is 2.47, indicating a considerable number of structure defects in NDG . The type H3 hysteresis loop of nitrogen adsorption–desorption isotherm (Figure S1f), suggesting the slit-shaped pores between parallel graphene layers of NDG. , The calculated Brunauer-Emmett- Teller (BET) specific surface area of NDG is 398 m 2 g –1 , verified that the NDG are the few-layer graphene sheets.…”
Section: Resultsmentioning
confidence: 75%
“…43−46 The intensity ratio of D to G is 2.47, indicating a considerable number of structure defects in NDG. 47 The type H3 hysteresis loop of nitrogen adsorption−desorption isotherm (Figure S1f), suggesting the slit-shaped pores between parallel graphene layers of NDG. 3,48 The calculated Brunauer-Emmett-Teller (BET) specific surface area of NDG is 398 m 2 g −1 , verified that the NDG are the fewlayer graphene sheets.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…2,3 By virtue of its extraordinary physicochemical properties, including large surface area, high conductivity, structural exibility and chemical stability, graphene has been intensively explored as an electrode material and/or a substrate of hybrid materials for high performance lithium ion batteries (LIBs). [4][5][6][7][8][9][10][11][12][13][14] It is commonly estimated that graphene might be more suitable for reversible lithium storage than commercial bulk graphite, because the graphene sheets could double the sorption capacity by binding the lithium ion on both sides of the graphene plane and by shortening the lithium diffusion distance. 4,5,[15][16][17][18][19][20] However, it is recently concluded that the lithium coverage on the surface of single layer graphene is actually smaller, because of the lower binding energies of lithium to carbon and the strong Coulombic repulsion of the lithium atoms on the opposite sides of graphene as well as the small charge transfer between lithium and graphene.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, LIBs are viewed as one of the most promising technology in various¯elds including the defense industry, space technology, electric vehicles and other¯elds. [1][2][3] Nowadays, commercial LIBs mainly use graphite as the anode material. However, graphite can hardly provide the high capacity and high energy density necessary to satisfy the demand required for high power application of the next-generation LIBs due to its low theoretical speci¯c capacity.…”
Section: Introductionmentioning
confidence: 99%